Third-party funding in international arbitration - Bench Nieuwveld, Lisa (Kluwer Law International, 2017)
Third-Party Funding in International Arbitration' reveals the nuances of third-party funding in international arbitration, examines the phenomenon in key jurisdictions, and provides a reliable resource for users and potential users who may wish to tap into and make use of this distinctive funding tool. Since the first edition of this book in 2012, third-party funding has become more mainstream in international arbitration practice. The second edition includes discussion of recent institutional developments as they relate to third-party funding, including the work of the ICCA-Queen Mary Task Force on third-party funding and how third-party funding is being incorporated into arbitral rules and investment treaties.